The Current Situation of the Parents of SEN Students in Lopburi Province, Thailand - Sermsap Vorapanya; Apison Pachanavon (International Journal of Pedagogy and Teacher Education, 2018)
The training aims at: 1) providing essential knowledge to parents of Special Educational Needs (SEN) students in inclusive primary schoolsin Lopburi Provinceand 2) learning the parents’ perspectives on how to presently work with their children with special needs. Eighty-five inclusive schools, from the first and the second school districts participated out of the pool of all regular public schools in LopburiProvince by suggesting parents’volunteer to participate in thesetraining sessions. Two parents of SEN students from each school were allowed to attend the trainings. The first school district had 80 parents attending from 40 inclusive schools, while the second school district had 89 parents joining the training from 45 inclusive schools, equating to 169 totalparticipating parents. Qualitative research reports from the parents’ sharing and brainstorming session emerged into three different themes accordingly: 1) knowing more rights and support for their children, 2) have better knowledge, increase awareness, and a better understanding for living with children with special needs, and 3) managing children with disabilities as if this was a result of their “Bad Karma.”